Formation of Bose–Einstein magnon condensate via dipolar and exchange thermalization channels - Bozhko, D.A.; Clausen, P.; Chumak, A.V.; Kobljanskyj, Yu.V.; Hillebrands, B.; Serga, A.A. (Физика низких температур, 2015)
Thermalization of a parametrically driven magnon gas leading to the formation of a Bose–Einstein condensate at the bottom of a spin-wave spectrum was studied by time- and wavevector-resolved Brillouin light scattering spectroscopy. Two distinct channels of the thermalization process related on dipolar and exchange parts of a magnon gas spectrum are clearly determined. It has been found that the magnon population in these thermalization channels strongly depends on applied microwave pumping power. The observed magnon redistribution between the channels is caused by the downward frequency shift of the magnon gas spectrum due to the decrease of the saturation magnetization in the course of injection of parametrically pumped magnons.